It?s not fair trade! - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
An economist in Zimbabwe?s Ministry of Agriculture summarises the reasons why developing country farmers struggle to sell their produce to foreign markets. He points out some of the progress that is being made in smallholder farming, and suggests the kind of opportunities available to farmers who want to boost their profits.